2004
DOI: 10.1016/j.femsle.2004.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analyses of the thermostable NAD+-dependent DNA ligase from Thermus filiformis

Abstract: The crystal structure of NAD+-dependent DNA ligase from Thermus filiformis (Tfi) revealed that the protein comprised four structural domains. In order to investigate the biochemical activities of these domains, seven deletion mutants were constructed from the Tfi DNA ligase. The mutants Tfi-M1 (residues 1-581), Tfi-M2 (residues 1-448), Tfi-M3 (residues 1-403) and Tfi-M4 (residues 1-314) showed the same adenylation activity as that of wild-type. This result indicates that only the adenylation domain (domain 1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 18 publications
3
12
0
Order By: Relevance
“…2C). This is in good agreement with recent observations for similar fragments from other NAD + -ligases [29,37]. Additional preliminary experiments confirmed that LigA lacking the BRCT domain (DBRCT-lig) could join double-strand breaks in plasmids, though at a much reduced rate compared to full LigA (data not shown).…”
Section: The Brct Domain Is Not Required For the Nick-joining Activitsupporting
confidence: 92%
See 3 more Smart Citations
“…2C). This is in good agreement with recent observations for similar fragments from other NAD + -ligases [29,37]. Additional preliminary experiments confirmed that LigA lacking the BRCT domain (DBRCT-lig) could join double-strand breaks in plasmids, though at a much reduced rate compared to full LigA (data not shown).…”
Section: The Brct Domain Is Not Required For the Nick-joining Activitsupporting
confidence: 92%
“…As discussed above, the detection of DNA binding by the BRCT domain of E. coli LigA confirms recent observations using LigA from thermophilic bacteria [29,37]. These studies are also consistent with previous analyses of NAD + -ligases from B. stearothermophilus and S. aureus, which showed that stable DNA binding was provided by a C-terminal fragment that contains the BRCT domain [8,31].…”
Section: Dna Binding By Nad + -Dependent Dna Ligasessupporting
confidence: 91%
See 2 more Smart Citations
“…More work is necessary to actually elucidate the role of this domain in detail. Its deletion resulted in threefold reduction in activity of E. coli LigA (Wilkinson et al, 2005), whereas the T. filiformis LigA retains activity even after its deletion (Jeon et al, 2004). In contrast, no activity, either in vitro or in vivo, is observed in the case of the M. tuberculosis enzyme.…”
Section: Brct Domain and Inhibitor Developmentmentioning
confidence: 97%